Alzheimer's disease biomarkers in Black and non‐Hispanic White cohorts: A contextualized review of the evidence. Issue 8 (6th December 2021) - Gleason, Carey E.; Zuelsdorff, Megan; Gooding, Diane C.; Kind, Amy J. H.; Johnson, Adrienne L.; James, Taryn T.; Lambrou, Nickolas H.; Wyman, Mary F.; Ketchum, Fred B.; Gee, Alexander; Johnson, Sterling C.; Bendlin, Barbara B.; et al.
Abstract: Black Americans are disproportionately affected by dementia. To expand our understanding of mechanisms of this disparity, we look to Alzheimer's disease (AD) biomarkers. In this review, we summarize current data, comparing the few studies presenting these findings. Further, we contextualize the data using two influential frameworks: the National Institute on Aging–Alzheimer's Association (NIA‐AA) Research Framework and NIA's Health Disparities Research Framework. The NIA‐AA Research Framework provides a biological definition of AD that can be measured in vivo. However, current cut‐points for determining pathological versus non‐pathological status were developed using predominantly White cohorts—a serious limitation. The NIA's Health Disparities Research Framework is used to contextualize findings from studies identifying racial differences in biomarker levels, because studying biomakers in isolation cannot explain or reduce inequities. We offer recommendations to expand study beyond initial reports of racial differences. Specifically, life course experiences associated with racialization and commonly used study enrollment practices may better account for observations than exclusively biological explanations.